Combustion Stability Analysis Using Vegetable Oil In Micro Gas Turbine Combustion Chamber - Nordin, Mohd Zuhairi (Universiti Sains Malaysia, 2019)
A micro gas turbine (MGT) is a power generator which is develop from gas turbine system. Conventionally, the MGT is running by using diesel and LPG. In rural area diesel fuel is difficult to get and very expensive. To secure a sustainable and poluution free environment, utilization of renewble fuels in micro gas turbine become a demand. Because of that, biofuel is being studied in term of it compatibility to replace diesel in micro gas turbine. The purpose of this project is to design and fabricate a side glass on the MGT combustion chamber. By having a side glass on the combustion chamber, combustion stability of various biofuels can be analyse physically and compared with combustion of diesel as benchmark. So, the best biofuel can be proposed to replace diesel in MGT in term of it performance and stability of combustion. The performance of the MGT is focussing on the power output, specific fuel consumption and emission of carbon monoxide (CO). The MGT is run at 3 different pressure and the temperature of compressor outlet, temperature of the turbine inlet and outlet, air flow rate and fuel flow are recorded. The discussion include the performance and stability analysis of the MGT with different input parameter which is the MGT pressure.